2014
DOI: 10.1175/mwr-d-13-00042.1
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis and Prediction of Microphysical States and Polarimetric Radar Variables in a Mesoscale Convective System Using Double-Moment Microphysics, Multinetwork Radar Data, and the Ensemble Kalman Filter

Abstract: Doppler radar data are assimilated with an ensemble Kalman Filter (EnKF) in combination with a double-moment (DM) microphysics scheme in order to improve the analysis and forecast of microphysical states and precipitation structures within a mesoscale convective system (MCS) that passed over western Oklahoma on 8–9 May 2007. Reflectivity and radial velocity data from five operational Weather Surveillance Radar-1988 Doppler (WSR-88D) S-band radars as well as four experimental Collaborative and Adaptive Sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Double-moment schemes contain prognostic equations for both mixing ratios and number concentrations of certain hydrometeor species, unlike single-moment schemes, which only contain prognostic equations for mixing ratios. Recent work indicates that double-moment schemes are necessary for reproducing dual-polarization signatures in ensemble Kalman filter analyses of supercells (Jung et al 2012) and MCSs (Putnam et al 2014). Additionally, Dawson et al (2010) obtained more accurate simulations of a tornadic supercell with two-and three-moment schemes, especially with the simulated cold pool.…”
Section: Methodsmentioning
confidence: 99%
“…Double-moment schemes contain prognostic equations for both mixing ratios and number concentrations of certain hydrometeor species, unlike single-moment schemes, which only contain prognostic equations for mixing ratios. Recent work indicates that double-moment schemes are necessary for reproducing dual-polarization signatures in ensemble Kalman filter analyses of supercells (Jung et al 2012) and MCSs (Putnam et al 2014). Additionally, Dawson et al (2010) obtained more accurate simulations of a tornadic supercell with two-and three-moment schemes, especially with the simulated cold pool.…”
Section: Methodsmentioning
confidence: 99%
“…Using this system, they analyzed the storm-scale features of the 27 April 2011 Alabama severe weather outbreak. Through assimilating radar and surface observations with an EnKF in combination with a double-moment microphysics scheme, Putnam et al (2014) analyzed the microphysical states and precipitation structures within a mesoscale convective system that passed over western Oklahoma during 8-9 May 2007. Schenkman et al (2011b) examined the impact of radar and Oklahoma Mesonet data assimilation on the prediction of mesovortices in a tornadic mesoscale convective system (MCS) through a three-dimensional variational data assimilation (3DVAR) system.…”
Section: Introductionmentioning
confidence: 99%
“…The ensemble filters have been used in operational global forecast systems to provide ensemble-based BEC (e.g., Raynaud et al 2011;Bonavita et al 2012;Hamill et al 2011b; as well as initial conditions for ensemble forecasts (e.g., Houtekamer et al 2005;Whitaker et al 2008;Hamill et al 2011a). The application of EnKF to mesoscale models has also enjoyed encouraging successes (e.g., Fujita et al 2007;Meng and Zhang 2007;Bonavita et al 2008) while for the convective scale, EnKF has shown great ability in dealing with complex, nonlinear physical processes (e.g., Tong and Xue 2005) that may even involve two-moment microphysics parameterization (e.g., Xue et al 2010;Jung et al 2012;Putnam et al 2014). Accurate representation of microphysical processes is especially important at the convective scale.…”
Section: Introductionmentioning
confidence: 99%